Development of race profiles for the performance of a simulated 2000-m rowing race - Kennedy, M. D.; Bell, G. J. (Canadian Journal of Applied Physiology, 2003)
The purpose of this study was to determine the race profile for a 2000-m simulated rowing race as well as the effect of training and gender on the race profile. Nineteen men and 19 women undertook a 2000-m simulated rowing race before and after 10 weeks of a typical off-season training program for rowing. Velocity was calculated every 200 m and the deviation in velocities from the mean race velocity (MRV) was plotted every 200 m to produce race profiles for each gender before and after training. The three fastest male rowers varied approximately 0.02 m.s from the MRV after training and displayed a constant-pace model. The fastest female rowers displayed an all-out strategy after training, producing large deviations from MRV. Average squared deviations from the mean (SDM) determined that all groups except the fastest females had a reduction in MRV deviation after training. These results suggest that the optimal race profile for a simulated 2000-m rowing race may be different between genders. Training reduces SDM and influences both male and female pacing patterns such that both exhibit a pacing strategy that is more similar to that of elite athletes in other events of similar and shorter duration.